How Primary School Children Perceive Tolerance by Technology Supported Instruction in Digital Transformation During Covid 19 - Sakalli, Özge; Altinay, Fahriye; Altinay, Mehmet; Dagli, Gokmen (Frontiers in Psychology, 2021)
Tolerance education started at an early age in primary schools for a multicultural life. Video-based educational applications provide that child actively participate and learn. This study aims to explore perceptions of primary school children towards tolerance by technology-enhanced learning in Covid 19 period. Online semi-structured interview form was used and the data were analysed with content analysis. Children developed the universal values such as equality, empathy, not harming themselves, being fair, helping others, happiness, smiling, hugging, respecting, giving gifts, loving people and all living beings without discrimination against disability by technological materials and online education. Future of education relies on tolerance education by incorporating universal values.